Productivity analysis for Vietnam's textile and garment industry - Thang, Nguyen; To, Trung-Thanh; Dat, Vu Hoang (The Philippine Review of Business and Economics, 2006)
The study uses firm-level panel data to study the technical efficiency performance of Vietnam's textile and garment firms in the period 1997-2000, as well as its determinants. The model used is that of Battese and Coelli [1995]. The average estimated technical efficiency of the two subsectors is relatively high. In the textile subsector, medium-old, South-based, private, export-oriented, and highly equipped firms are found to be more technically efficient than those with differing characteristics. In the garment subsector, large or old-medium, south-based, and high external capital firms have higher technical efficiency. Meanwhile, small, old, and highly equipped firms have lower technical efficiency than firms with other characteristics. The total factor productivity (TFP) picture of the textile subsector is mixed, whereas the TFP growth of the garment subsector is positive, although this growth decreases.